A contribution to Heteroptera (Hemiptera) of Arasbaran and Vicinity, Northwestern Iran - Ghahari, Hassan (2010)
A list of Heteroptera collected from Arasbaran Biosphere Reserve (East Azarbayjan Province, northwestern Iran) and neighboring areas is provided. A total of 114 species from 87 genera and 19 families were collected from Arasbaran and vicinity. Two species are new records for Iran: Gerris (Gerris) maculatus Tamanini and Sigara (Vermicorixa) lateralis (Leach).